Intravenous butorphanol as an adjunct to patient-controlled epidural analgesia with ropivacaine and sufentanil in labor: a randomized controlled study - Ting Zhou; FengYuan Nong; MengXia Wang; ZhaoJia Liang; YaLan Li (IMR Press, 2022)
Background: Butorphanol was safely used for obstetric analgesia for many years. We attempted to determine if it increases the analgesic effect during patient-controlled epidural labor analgesia (PCEA) and if it affects the labor-process. Methods: Term pregnant women (N = 60) were randomly assigned to two groups, to receive either 1 mg intravenously butorphanol or 10 mL normal saline as placebo at 10 min before intrathecal anesthesia. Pain score, duration of first and second stage of labor, mode of delivery, umbilical artery blood gas, Apgar scores and adverse effects were recorded. Result: Butorphanol shortened the duration of the second stage of labor (t = -2.41, p = 0.019). Women in butorphanol group showed significantly increased incidence of pruritus (x2 = 20.32, p = 0.000), but they also showed significantly increased incidence of the adverse events such as maternal somnolence and dizziness (x2 = 8.366, p = 0.004; x2 = 26.447, p = 0.000 respectively). The pain scores of the two groups showed a linear reduction within 1 h (F = 8.878, p = 0.004), and from intravenous injection of butorphanol to the 5th minute after intrathecal analgesia, the analgesic scores of butorphanol group were significantly lower than those of placebo group (p < 0.05). At the third hour after intrathecal injection, the Visual analogue scale (VAS) score was significantly lower in butorphanol group than placebo group (95% Confidence Interval (CI) -3.02 to -0.28; t = -2.51, p = 0.021). Conclusions: i.v. butorphanol 1 mg alleviates the labor pain during intrathecal puncture, and It will be easier to get the cooperation of pregnant women and shortens the second stage of labor. It effectively relieved the pruritus, but increased the incidence of dizziness and somnolence.